2012
DOI: 10.1242/bio2012604
|View full text |Cite
|
Sign up to set email alerts
|

Histological and MS spectrometric analyses of the modified tissue of bulgy form tadpoles induced by salamander predation

Abstract: SummaryThe rapid induction of a defensive morphology by a prey species in face of a predation risk is an intriguing in ecological context; however, the physiological mechanisms that underlie this phenotypic plasticity remain uncertain. Here we investigated the phenotypic changes shown by Rana pirica tadpoles in response to a predation threat by larvae of the salamander Hynobius retardatus. One such response is the bulgy morph phenotype, a relatively rapid swelling in size by the tadpoles that begins within 4 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…The pirica protein was found to contain a zona pellucida domain similar to proteins that function to control water permeability; the pirica gene was shown to be expressed in the superficial epidermis of the tadpole skin [ 29 ]. We also demonstrated that water retention in the connective tissue and maintenance of a constant osmotic pressure were important factors for bulgy morph formation, supporting the interpretation that predator-induced expression of pirica in the skin causes retention of absorbed water [ 30 ]. The immuno-related proteins hyaluronic acid, histone H3 and 14-3-3 zeta were the most abundant constituents of the liquid aspirated from the connective tissue.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The pirica protein was found to contain a zona pellucida domain similar to proteins that function to control water permeability; the pirica gene was shown to be expressed in the superficial epidermis of the tadpole skin [ 29 ]. We also demonstrated that water retention in the connective tissue and maintenance of a constant osmotic pressure were important factors for bulgy morph formation, supporting the interpretation that predator-induced expression of pirica in the skin causes retention of absorbed water [ 30 ]. The immuno-related proteins hyaluronic acid, histone H3 and 14-3-3 zeta were the most abundant constituents of the liquid aspirated from the connective tissue.…”
Section: Introductionsupporting
confidence: 79%
“…This gene showed opposite responses in tadpoles of the dragonfly and salamander treatment groups (Figure 8 b): a 6.6 fold increase was seen in the salamander treatment group, while a 6.5 fold increase occurred following the removal of the dragonfly larvae compared to control. In the salamander treatment, tadpoles maintain their osmotic pressure by uptake of Na and Cl ions to increase the amount of bodily fluids for bulgy morph formation [ 30 ]. Possibly, non-motile or sensory cilia may be involved in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purifi ed fraction (0.22 g) diluted in a sample buffer containing SDS and 2-mercaptoethanol was boiled and electrophoresed on a 15% polyacrylamide gel. Mass spectrometric analysis and the pretreatment were performed as described previously ( 29 ). Briefl y, protein in the gel was detected by MS-compatible silver staining.…”
Section: Protein Analysismentioning
confidence: 99%
“…Low digestibility proteins were analyzed and identified using a mass spectrometer, as previously described by Mori et al [31] . In brief, proteins (spots) were excised from the gel, destained, and the thiol groups of cysteines alkylated by iodoacetamide.…”
Section: Methodsmentioning
confidence: 99%